Chemical Composition, Fatty Acids Content and Glycemic Index of Two Different Types of Omani Halwa - Ali, Amanat; Al-Zuhaibi, Khalid M.; Waly, Mostafa I.; Al-Alawi, Ahmed A.; Al-Sabahi, Jamal N.; Sankar, Devarajan (Pakistan Journal of Nutrition, 2013)
The study evaluated the chemical composition, fatty acids contents and Glycemic Index (GI) of two different types (white and black) of Omani halwa. Representative samples of Omani halwa were collected from the local market. The proximate composition and energy contents of white and black halwa did not vary significantly (p